Diversion of Flow and Sediment Toward a Side Channel Separated From a River by a Longitudinal Training Dam. Issue 6 (5th June 2020) - de Ruijsscher, T. V.; Vermeulen, B.; Hoitink, A. J. F.
Abstract: A human‐made entrance to a side channel separated from the river by a longitudinal training dam can be considered a new, emergent type of river bifurcation. To understand the processes controlling the diversion of flow and sediment toward the side channel at such bifurcations, a comprehensive field monitoring program was performed in the Waal River, which is the main branch of the Rhine River in the Netherlands. Local processes govern the flow field in the bifurcation region. The angle between the main river flow and the flow into the side channel increases with decreasing lateral and longitudinal distance to the bifurcation point, which corresponds to the head of the training dam. The general flow pattern can be well reproduced with a uniform depth, potential flow model consisting of a superposition of main channel flow and lateral outflow. For submerged flow conditions over the sill, the side channel hydraulic conditions influence the exchange processes, yet free flow side weir theory describes the flow field at this bifurcation type qualitatively well. The vertical flow structure in the side channel, which governs the sediment exchange between the main channel and the side channel, is steered by the geometrical details of the sill. The presence of the sill structure is key to controlling the morphological stability of this type of bifurcation given its primary influence on bed load sediment import and exerts an indirect impact on suspended sediment exchange. Key Points: Depth variation of the flow at the intake of a side channel with a constructed sill is steered by the geometry of the sill Horizontal flow pattern in the side channel entrance region is qualitatively similar to free flow over a sharp‐crested side weir A constructed sill is of vital importance for the morphological stability of the side channel behind a longitudinal training dam